Presence of the Reflective and Critical Thinking Capacity in Nursing Curricula in Iberian America - Lucila Cárdenas Becerril (Universidad de Antioquia, 2020)
Objective. The objective was to identify the presence of the capacity for reflexive-critical thinking or similar, in Nursing Curricula in Iberian America.